The accumulation and trapping of grains at planet gaps: Effects of grain growth and fragmentation. (October 2015) - Gonzalez, J.-F.; Laibe, G.; Maddison, S.T.; Pinte, C.; Ménard, F.
Abstract: We model the dust evolution in protoplanetary disks with full 3D, Smoothed Particle Hydrodynamics (SPH), two-phase (gas+dust) hydrodynamical simulations. The gas+dust dynamics, where aerodynamic drag leads to the vertical settling and radial migration of grains, is consistently treated. In a previous work, we characterized the spatial distribution of non-growing dust grains of different sizes in a disk containing a gap-opening planet and investigated the gap's detectability with the Atacama Large Millimeter/submillimeter Array (ALMA). Here we take into account the effects of grain growth and fragmentation and study their impact on the distribution of solids in the disk. We show that rapid grain growth in the two accumulation zones around planet gaps is strongly affected by fragmentation. We discuss the consequences for ALMA observations. Abstract : Highlights: We model dust trapping at planet gap edges in a protoplanetary disk. We focus on the effects of growth and fragmentation on the dust dynamics. We find that large fragmentation thresholds are required for planetesimal formation. Constraining the value of the threshold is difficult from mm observations only.